The status of Philippine textile industry - Mauricio, Rachel Hannah H. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT For an industry that was once something to be proud of, and one that should provide for one of the three of man's most basic needs, it is a wonder what happened to the textile industry, where it is now, where it is headed. The Philippines was once a country that could boast of the vibrance of its textile industry (S.B. 1133 (2010)). The industry, equipped with highly skilled and educated workers, was greatly supported by the government (Ong, 2012). Since the 1960s, the textile industry has struggled (Austria, 1994) and declined in size due to cheaper suppliers in the domestic and global market (United States International Trade Commission). The study covered the present condition of the textile industry of the Philippines through guided interviews with key persons in the industry. The analysis of the study was based on the gathered information, and documents acquired from the respondent, with verifications from both online and printed sources. This primal research on the Philippine textile industry discussed the state of the industry in three aspects: the structure of the industry, the performance of the industry, and the supply of the industry. It also identified certain recent and ongoing movements in the Philippine textile industry. The study was able to list some of the concerns currently surrounding the industry. The Philippine textile industry is firstly, strongly linked to the local agriculture and agri-business sectors due to the Philippine tropical fibers that are being incorporated in textiles, and to the local garment sector, which processes most of the local textile output into uniformed; and secondly, involved in many partnerships within the private sector and with the public departments, and in negotiations with other countries; because thirdly, it has been growing weak in itself, based on the industry's economic contributions.